Alloreactive memory B cell detection by flow cytometric cross match using polyclonally activated memory B cell culture supernatants - (:unkn) unknown (My University, 2022)
In addition to alloantibodies, alloreactive memory B cell (mBC) evaluation has a potential for immunological risk assessment during transplantation processes. For the alloreactive mBCs evaluation currently, direct Flow Cytometric (FC) analysis using the HLA tetramer staining is an option. Evaluation of alloantibodies produced by the polyclonally stimulated alloreactive mBCs in in vitro culture system seems to be another useful approach, but this needs further downstream applications. In this study, we investigated the usefulness of the Flow Cytometric Cross Match (FCXM-supernatant) in which in vitro polyclonally activated mBCs culture supernatants and potential donor\"s lymphocytes being used for the mBC detection. FCXM-supernatant assays were performed between culture supernatants of polyclonally activated mBCs obtained from 4 allosensitized multiparous women and 14 renal transplant patients, and their non-alloimmunized spouses\" or donors\" lymphocytes, and vice versa. HLA typing was performed by SSP method. Anti-HLA antibodies produced by in vitro activated alloreactive mBCs were also evaluated by the Luminex assays. The success of in vitro polyclonal activation of mBCs was evaluated by a total IgG ELISA test and antibody secreting cell analyses by FC. Donor specific alloreactive mBCs were detected by FCXM-supernatant in 45% of the 18 allosensitized cases. Detection rate was 85% (6 out of 7) in the strongly allosensitized cases. No alloreactive mBCs was detected in control cases without allosensitization. FCXMsupernatant negative results of the allosensitized cases were related to low level of allosensitization and insufficient polyclonal stimulation evaluated by total IgG antibody tests of the supernatants. We herein report a practical methodology for alloreactive mBC detection as a donor specific manner using the FCXM-supernatant assay so that this would easily be transformed into a routine test performed in tissue typing laboratories.
Keywords: Tıp; Sağlık Bilimleri; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Life Sciences; Natural Sciences; İmmünoloji; Yaşam Bilimleri (LIFE); TRANSPLANTASYON; Klinik Tıp; Klinik Tıp (MED); IMMUNOLOGY; Life Sciences (LIFE); TRANSPLANTATION; CLINICAL MEDICINE; Clinical Medicine (MED); Genel İmmünoloji ve Mikrobiyoloji; Transplantasyon; General Immunology and Microbiology; Immunology; Transplantation; Flow cytometric cross match; Alloreactive memory B cell; Culture supernatants; Polyclonal activation; HUMORAL REJECTION; HLA; QUANTIFICATION